ANALYSIS OF DISPUTES JURIDICAL POLICE INVESTIGATORS AUTHORITY OF THE REPUBLIC OF INDONESIA THE ANTI CORRUPTION COMMISSION ON CRIME CORRUPTION LICENSE DRIVING SIMULATOR - Lading, Frans (Journal of Humanity, 2014)
Criminal acts of corruption in Indonesia is widespread within the community. Its development continued to increase from year to year, the number of cases from both and the amount of the financial loss to the State, as well as in terms of the quality of the criminal acts carried out increasingly systematic in scope as well as entering all aspects of peoples lives. The increased criminal acts of corruption which cannot be controlled would bring disaster not only to the life of the national economy but also, on the life of nation and State in General. Criminal acts of corruption were widespread and systematic as well a breach of the rights to social and economic rights of the community, and therefore all the criminal acts of corruption can no longer be classed as ordinary crimes, but rather has become an extraordinary crime. So in an effort can no longer be done on a regular, but prosecuted ways extraordinary.